Auditory and Visual Attention Performance in Children With ADHD: The Attentional Deficiency of ADHD Is Modality Specific. (August 2017) - Lin, Hung-Yu; Hsieh, Hsieh-Chun; Lee, Posen; Hong, Fu-Yuan; Chang, Wen-Dien; Liu, Kuo-Cheng
Objective: This study explored auditory and visual attention in children with ADHD.Method: In a randomized, two-period crossover design, 50 children with ADHD and 50 age- and sex-matched typically developing peers were measured with the Test of Various Attention (TOVA).Results: The deficiency of visual attention is more serious than that of auditory attention in children with ADHD. On the auditory modality, only the deficit of attentional inconsistency is sufficient to explain most cases of ADHD; however, most of the children with ADHD suffered from deficits of sustained attention, response inhibition, and attentional inconsistency on the visual modality. Our results also showed that the deficit of attentional inconsistency is the most important indicator in diagnosing and intervening in ADHD when both auditory and visual modalities are considered.Conclusion: The findings provide strong evidence that the deficits of auditory attention are different from those of visual attention in children with ADHD.